VD_FINDINFO HC / 2013 / 202 vom 25. März 2013 - VD Tribunal cantonal (2013)
EXPULSION DE LOCATAIRE, PROCÉDURE SOMMAIRE | 257d al. 1 CO, 257d al. 2 CO, 257d CO, 248 CPC (CH), 257 CPC (CH), 319 CPC (CH), 319 let. a CPC (CH), 322 al. 1 CPC (CH), 322 CPC (CH)